Cardiac Disorders in Patients with Ischemic Stroke - Bikram Prasad Gajurel ,; Anju Gurung,; Rajeev Ojha,; Reema Rajbhandari,; Ragesh Karn, (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTIONWorldwide cardioembolic strokes account for one third of non-lacunar strokes and almost half of all risk factors of ischemic stroke in Nepal. This study was done to describe the types of cardiac disorders and their associations with younger and older patients with ischemic stroke.MATERIAL AND METHODSIn this prospective observational study, data were collected by convenience sampling and analyzed by the Statistical Package for the Social Sciences version 26. Cardiac disorders were divided into rhythm disturbances and structural disorders. Patients were divided into younger (≤ 50 years) and older (> 50 years) patients based on standard deﬁnition. The associations were analyzed by using Chi-square test. Other data were expressed as frequencies and percentages.RESULTSOf 145 patients were included, cardiac disorders were present in 88.3%. Cardiac structural disorders were present in 86.2% out of which the commonest were left ventricular hypertrophy (26.2%), left ventricular diastolic dysfunction (23.4%) and mitral stenosis (13.8%). Cardiac rhythm abnormalities were present in 42.1% and atrial ﬁbrillation (17.2%), atrial ectopics (14.5%) and ventricular ectopics (4.8%) were the commonest. When considered in total, there was no statistically signiﬁcant differences in the distribution of these disorders between young and old patients. However, mitral stenosis was strongly associated with young patients (p=0.001). Atrial ﬁbrillation and older patients were also signiﬁcantly associated (p=0.04).CONCLUSIONThough common, cardiac disorders in total were not signiﬁcantly associated with young and older patients with ischemic stroke; however, mitral stenosis was signiﬁcantly associated with young patients and atrial ﬁbrillation with older patients.